Higher normal ranges of urine albumin-to-creatinine ratio are independently associated with carotid intima-media thickness - Kweon, Sun-Seog (BioMed Central, 2012)
BACKGROUND: High normal values of urine albumin-to-creatinine ratio (UACR) have been reported to have predictive values for hypertension, incident stroke, and higher mortality in the general population. This study aimed to investigate the association between normal ranges of UACR and carotid intima-media thickness (CIMT) in adult population. METHODS: We performed a cross-sectional study in adults aged 45 to 74 years who were living in Namwon City, South Korea. Both common CIMTs were measured, and mean values were calculated. Normal values of UACR were defined as <30mg/g and categorized into quintiles; less than 6.50, 6.51-9.79, 9.80-13.49, 13.50-18.89, and more than 18.90 mg/g. The association between the quintiles of UACR and common CIMT was analyzed and stratified by sex. RESULTS: A total of 7555 participants (3084 men and 4471 women) with normal UACR were enrolled in the present study. Common CIMT was positively and independently associated with increasing quintiles of UACR in men and women, even after adjusting for potential confounders including age and cardiovascular risk factors. Compared to the first quintile, the fifth quintile showed odds ratios of 1.80 (95% confidence intervals, 1.26-2.55) and 1.97 (1.28-3.04) for increased CIMT (>0.9mm) in men and women, respectively. CONCLUSION: Higher UACR values within normal ranges (<30 mg/g) were positively and independently associated with CIMT in a Korean general population, suggesting that higher normal values of UACR might be a risk marker of subclinical carotid atherosclerosis.